2005
DOI: 10.1111/j.1462-5822.2004.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of CD46 and α5β1 integrin by group A streptococci is required for efficient invasion of epithelial cells

Abstract: SummaryMembrane cofactor protein (MCP or CD46), a widely distributed complement regulatory human protein, is a cell surface receptor for many pathogens including group A streptococci (GAS). The surface M protein of GAS binds CD46 and mediates GAS adherence to keratinocytes. In the present study, we studied the role of CD46 in GAS invasion of human lung epithelial cells, A549. Anti-CD46 antibody which specifically blocks the domain to which M protein binds inhibited adherence to and invasion of A549 cells by GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 37 publications
(55 reference statements)
2
53
0
Order By: Relevance
“…Interestingly, the expression of ␤1 integrin was slightly reduced at 24 h (Fig. 1C), supporting that CD46 is linked to ␤1 integrin, as was previously reported (38). Control experiments showed that bacteria pretreated with ethanol or heat did not mediate the loss of CD46 in FaDu cells, suggesting that the process required viable bacteria (data not shown).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Interestingly, the expression of ␤1 integrin was slightly reduced at 24 h (Fig. 1C), supporting that CD46 is linked to ␤1 integrin, as was previously reported (38). Control experiments showed that bacteria pretreated with ethanol or heat did not mediate the loss of CD46 in FaDu cells, suggesting that the process required viable bacteria (data not shown).…”
Section: Resultssupporting
confidence: 68%
“…These data suggest that human CD46 plays an important role during S. pyogenes infection. CD46 serves as a receptor for several pathogens including strains of measles virus (10), human herpesvirus type 6 (42), group A streptococci (38), adenovirus (13,45), and Neisseria (24). Among these pathogens, infection by certain strains of measles virus (33,43), human herpesvirus type 6 (42), serogroup B adenovirus (41), and Neisseria gonorrhoeae (15) has been shown to cause CD46 downregulation from the cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surface-exposed proteins are best positioned to be major contributors of host cell invasion, and antibodies against such proteins have been shown to be effective at blocking invasion (26,28). NlpC contains invasion-associated domains in addition to the P60 domain mentioned in the introduction.…”
Section: Discussionmentioning
confidence: 99%